2020
DOI: 10.1177/0950422220904932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of construction industry support for PhD projects: The case of a Swedish scheme

Abstract: One of the many varieties of university–industry collaboration is industry engagement in doctoral programmes. A scheme operated by the Development Fund of the Swedish Construction Industry since the early 1990s has supported thesis projects for about 150 PhD candidates. While they were doctoral students they were employed by contractors as industrial doctoral candidates or by universities. The purpose of this investigation was to analyse how, as PhD graduates, they perceived the benefits of doctoral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Compared to traditional science, technology, engineering and mathematics disciplines, construction management is a comparatively immature ‘technical-based’ discipline that developed out of the advancements of the post-war era, driven by the need to rebuild infrastructure to aid economic recovery (Charted Institute of Building, 2021; Howell et al, 2011). As with most technical-based programmes, in the content taught an equilibrium must be achieved between contemporary industrial relevance and academic rigour, couched within an ever-changing construction and academic topologies (Borg and Scott-Young, 2020; Brochner and Sezer, 2020). Just as a project plan and schedule are essential tools for the successful construction of a building, so too is curriculum development for a construction management programme.…”
mentioning
confidence: 99%
“…Compared to traditional science, technology, engineering and mathematics disciplines, construction management is a comparatively immature ‘technical-based’ discipline that developed out of the advancements of the post-war era, driven by the need to rebuild infrastructure to aid economic recovery (Charted Institute of Building, 2021; Howell et al, 2011). As with most technical-based programmes, in the content taught an equilibrium must be achieved between contemporary industrial relevance and academic rigour, couched within an ever-changing construction and academic topologies (Borg and Scott-Young, 2020; Brochner and Sezer, 2020). Just as a project plan and schedule are essential tools for the successful construction of a building, so too is curriculum development for a construction management programme.…”
mentioning
confidence: 99%
“…It is independent research about a specific research area with the guidance of a set of supervisors and most often, explores about real-world issues. A lot of postgraduate research is industry related and based on case studies; thus, have most of project-based learning characteristics (Bröchner and Sezer, 2020).…”
Section: Project-based Learningmentioning
confidence: 99%
“…Subscales of general scientific competencies (Grab-Kroll et al, 2019), and universal skills (Luo et al, 2018) were identified. Two other studies (Walker and Yoon, 2017;Bröchner and Sezer, 2020) provided nominal information on the scales utilized, with insufficient detail to identify what domains were covered. The scales were either adapted from other studies (Allgood et al, 2018;Shih et al, 2019;Bröchner and Sezer, 2020), or self-developed for the study (Walker and Yoon, 2017;Luo et al, 2018;Grab-Kroll et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two other studies (Walker and Yoon, 2017;Bröchner and Sezer, 2020) provided nominal information on the scales utilized, with insufficient detail to identify what domains were covered. The scales were either adapted from other studies (Allgood et al, 2018;Shih et al, 2019;Bröchner and Sezer, 2020), or self-developed for the study (Walker and Yoon, 2017;Luo et al, 2018;Grab-Kroll et al, 2019). Shih et al (2019) was the only study to report on psychometric properties.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation